Motor outcomes in individuals born small for gestational age at term: a systematic review - Hoda Taiar; Silje Dahl Benum; Kristina Anna Djupvik Aakvik; Kari Anne I. Evensen (BMC, 2024)
Abstract Background Being born small for gestational age (SGA) is a risk factor for motor difficulties. Previous reviews exploring this topic are mostly focused on children born preterm. We aimed to review the literature to determine the association between being born SGA at term and motor outcomes. Methods PubMed and Embase were searched for relevant articles without any restrictions on publication year or participants' age. Inclusion criteria were SGA exposure at term (≥ 37 weeks of gestation), cohort studies or randomized controlled trials with motor outcome assessed by standardized motor tests with results reported as continuous scores (mean/median) compared with a control group. Exclusion criteria were abstracts, editorials and commentaries, articles in non-English language or no full text available. Reviews were screened for relevant articles. Quality of included studies was assessed by the Newcastle-Ottawa Scale. Results In total, 674 records were identified by the literature search and screened by two independent authors. Thirteen original articles were eligible and included in a qualitative synthesis, and five (38%) of these were included in a meta-analysis. Nine (69%) studies were from high-income countries. Most studies were carried out in early childhood, and only one study in adulthood. Seven (54%) articles reported that individuals born SGA at term had poorer scores on standardized motor tests compared with controls, while no differences were reported in five (38%) articles. One article did not report p-values, although the differences were comparable to the other studies. Group differences were of small to moderate effect size (0.19 to 0.65 standard deviation units). The pooled effect size was -0.43 (95% confidence interval: -0.60 to -0.25). Adjustment for covariates were reported in seven (54%) articles and did not change the results. Proportions of motor difficulties, reported in five (38%) articles, ranged from 8.9 to 50% in individuals born SGA from infancy to adolescence. Conclusions This systematic review shows that being born SGA, also at term, may be a risk factor for poorer motor outcomes throughout childhood, confirmed by a meta-analysis in early childhood. Further research is needed to establish the risk of adult motor difficulties in individuals born SGA at term.